Changes of photosynthetic parameters in wheat/barley introgression lines during salt stress - Dulai, Sándor; Molnár, István; Molnár-Láng, Márta (Acta Biologica Szegediensis, 2011)
Salt stress induced photosynthetic responses were investigated in the wheat/barley introgression lines developed in the Agricultural Research Institute, Martonvásár, Hungary, and in different parental wheat and barley Hordeum vulgare L. genotypes. An increase in NaCl concentration of the nutrient solution to 200 mmol L-1 resulted in a considerable stomatal closure and a decreased net CO2 assimilation rate (A) for wheat genotypes, barley cv. Betzes and 4H Asakaze komugi-Manas addition line while changes of these parameters were less significant for barley cv. Manas and the 7H Asakaze komugi-Manas and 6H Mv9 kr1-Betzes-Seneca addition lines. These preliminary results suggest that the 7H Akom-Manas addition line may be a good candidate for improving the salt tolerance of wheat in the future.